Overweight and obesity affect skeletal maturation and dental development in children and adolescents – a retrospective study - Katarzyna Olszewska; Maria Mielnik-Błaszczak; Paula Plechawska; Joanna Przybyś (Journal of Education, Health and Sport, 2018)
Introduction: There are many questions concerning the relationship between childhood obesity and childhood growth and development. The aim of the study was to determine if overweight and obese children and adolescents show accelerated dentition development and skeletal maturity in comparison with the normal weight individuals. Material and Methods: In total, 109 patients divided into three groups were selected for the retrospective study. The OW group included 34 overweight patients (mean age: 10.91 ± 2.43). The OB group comprised 23 obese individuals (mean age: 10,67 ± 2.54). The control group (NW) included 52 normal weight subjects (mean age: 10.19 ± 1.81). Dental age and skeletal maturity were assessed. The data was analyzed by STATISTICA 10 for Windows Software (StatSoft Inc., Tulsa, USA). Results: The mean dental age acceleration was 0.38 ± 1.13 in the NW group, 1,79 ± 0.96 in the OW group and 1.88 ± 0.75 in the OB group and was significantly greater in the OW and OB group than in the NW group (P